Design Of Kenaf Fiber Polymer Composite For Interior Car Door Panel Application - Zulkifili, Al Azim Faiz (Universiti Sains Malaysia, 2022)
Recently, natural fibers have gained popularity among researchers, engineers, and scientists as alternative reinforcing materials used in manufacturing polymer composites, especially in the automotive industry. In the automotive industry, the use of natural fibers provides many advantages over synthetic conventional components such as low cost, low density, abrasion resistance, recyclability, renewability, and eco-efficiency. However, many natural fiber composites available today are not designed for one specific application cause the mechanical properties of the composites are not suitable to use in certain automotive components such as inner door panels. This project aims to study and fabricate the kenaf fiber composite to use as an inner door panel in an automotive application. The effects of kenaf fibers orientation in the composites on the mechanical properties such as tensile and flexural strength were investigated in this project. Kenaf fibers were arranged in random orientation and unidirectional (0°) orientation before it undergoes the hand layup and vacuum bagging process to produce the composite samples. After that, tensile and flexural tests were done on the composite samples following the designated ASTM standards. In this study, it was found that the presence of kenaf fibers were increasing the tensile strength and flexural strength of the composite by transferring loads between fibers and giving the composite its net shape. In addition, for the natural fiber orientation, the unidirectional orientation of kenaf fibers can drastically increase the tensile and flexural strength of the composite compared to the random orientation of kenaf fibers. The unidirectional orientation increases mechanical properties because of its aspect ratio is good enough and the fibers are aligned making the load can transfer equally between the fibers.